2021
DOI: 10.1016/j.dsx.2021.102189
|View full text |Cite
|
Sign up to set email alerts
|

“Vitamin D supplementation and COVID-19 treatment: A systematic review and meta-analysis”

Abstract: Background Vitamin-D is an immune-modulator which might be linked to disease severity by SARS-CoV-2. Methods Meta-analysis of RCTs and quasi-experimental studies, evaluating the role of vitamin-D supplementation in COVID patients was done. Results Total 5 studies (3 RCTs and 2 Quasi-experimental) including n = 467 patients were included. Vitamin D didn't reduce mortality (RR 0.55, 95%CI 0.22 to 1.39, p = 0.21), ICU admission rates (RR 0.20, 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(94 citation statements)
references
References 33 publications
2
87
1
4
Order By: Relevance
“…This could be explained by the fact that a deficiency of a certain vitamin may not necessarily indicate a disease process, rather it might be an outcome. In addition, the administration of vitamins after diagnosis of SARS-CoV-2 infection may not be as effective as a physiological replenished state before the diagnosis [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…This could be explained by the fact that a deficiency of a certain vitamin may not necessarily indicate a disease process, rather it might be an outcome. In addition, the administration of vitamins after diagnosis of SARS-CoV-2 infection may not be as effective as a physiological replenished state before the diagnosis [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Il-6, TNF), interferon, and chemokines ( Greiller and Martineau, 2015 ). A meta-analysis published by Rawat et al, examining the use of vitamin D in patients with COVID-19 demonstrated no significant reduction in mortality, ICU admission, or the need for invasive ventilation in patients receiving vitamin D supplementation ( Rawat et al, 2021 ).…”
Section: Other Agents Tested For Potential Efficacy In Treating Covid-19 Infectionmentioning
confidence: 99%
“… Drug No. patients Outcome Effect Vitamin D ( Rawat et al, 2021 ) 467 Mortality reduction No effect; R = 0.55 (95% CI 0.22 - 1.39), p = 0.21 HCQ ( Amani et al, 2021 ) 6,059 Mortality reduction No effect, RR = 0.7 (95% CI: 0.24 - 1.99) HCQ ( Bartoszko et al, 2021 ) 8,161 Side effects RR = 1.81 (95% CI: 1.36 - 2.42), p < 0.05 HCQ ( Axfors et al, 2021 ) 10,012 Increase of mortality OR = 1.11 (95% CI: 1.02 - 1.20) Convalescent plasma ( Bansal et al, 2021b ) 27,706 Mortality reduction OR 0.76 (95% CI: 0.53–1.08), p = 0.13 Sarilumab ( Lescure et al, 2021b ) 416 Positive effect HR = 1.03 (95% CI 0.75 - 1.40]; p = 0.96 Legend: HCQ – hydroxychloroquine; HR – hazard ratio; OR – odds ratio; RR – risk ratio; 95% Cl – 95 % confidence interval …”
Section: Other Agents Tested For Potential Efficacy In Treating Covid-19 Infectionmentioning
confidence: 99%
“…Based on these and similar studies, it was suggested that vitamin D supplementation of the general population might reduce the viral spread and decrease the disease severity and thereby aid in tackling the SARS-CoV-2 pandemic (1,3,5,6,(10)(11)(12). However, recent meta-analyses found that the evidence to support vitamin D supplementation for the prevention or treatment of COVID-19 was inconclusive (13)(14)(15). In line with this, a randomized, double-blind, placebocontrolled trial found that vitamin D supplementation did not reduce the overall risk of acute respiratory tract infection in general (16).…”
Section: Introductionmentioning
confidence: 99%